Dosage of Treatment to Sexual Offenders: Are We Overprescribing? - Looman, Jan; Serin, Ralph C.; Cousineau, C.; Malcolm, Bruce (International journal of offender therapy and comparative criminology, 2003)
A sample of 337 offenders who received treatment in a variety of sex offender treatment programs in the Ontario region of Correctional Service Canada between 1993 and 1998 were divided based on the highest intensity sex offender programming that they received low, moderate, and high. The three groups were compared with reference to a variety of actuarial risk assessment measures, criminogenic factors, and the number and type of treatment programs completed. It was hypothesized that the high-intensity group would have more criminogenic risk factors, higher actuarial scores, and participate in more treatment programs than both the moderate- and low-intensity groups. The results indicate that in general, the hypotheses were supported. Nonetheless, the results suggest that the low-intensity group may be receiving too much sex offender-specific treatment